Immunogenicity of BNT162b2 COVID-19 vaccine in New Zealand adults. Issue 34 (12th August 2022) - Priddy, Frances H.; Williams, Michael; Carson, Simon; Lavender, Brittany; Mathieson, Julia; Frampton, Chris; Moreland, Nicole J.; McGregor, Reuben; Williams, Georgia; Brewerton, Maia; Gell, Katie; Ussher, James; et al.
Abstract: Background: There is very little known about SARS-CoV-2 vaccine immune responses in New Zealand populations at greatest risk for serious COVID-19 disease. Methods: This prospective cohort study assessed immunogenicity in BNT162b2 mRNA vaccine recipients in New Zealand without previous COVID-19, with enrichment for Māori, Pacific peoples, older adults ≥ 65 years of age, and those with co-morbidities. Serum samples were analysed at baseline and 28 days after second dose for presence of quantitative anti-S IgG by chemiluminescent microparticle immunoassay and for neutralizing capacity against Wuhan, Beta, Delta, and Omicron BA.1 strains using a surrogate viral neutralisation assay. Results: 285 adults with median age of 52 years were included. 55% were female, 30% were Māori, 28% were Pacific peoples, and 26% were ≥ 65 years of age. Obesity, cardiac and pulmonary disease and diabetes were more common than in the general population. All participants received 2 doses of BNT162b2 vaccine. At 28 days after second vaccination, 99.6% seroconverted to the vaccine, and anti-S IgG and neutralising antibody levels were high across gender and ethnic groups. IgG and neutralising responses declined with age. Lower responses were associated with age ≥ 75 and diabetes, but not BMI. The ability to neutralise the Omicron BA.1 variant in vitro was severely diminished but maintained against other variants of concern. Conclusions: Vaccine antibody responses to BNT162b2 were generally robust and consistent with international data in this COVID-19 naïve cohort with representation of key populations at risk for COVID-19 morbidity. Subsequent data on response to boosters, durability of responses and cellular immune responses should be assessed with attention to elderly adults and diabetics.